Production of Cellulose Nitrate Polymer from Sawdust - I. M. Adekunle (E-Journal of Chemistry)
Cellulose nitrate polymer was produced from sawdust of Nigeria origin using a method, which involved alternate alkaline and chlorination treatment to remove non-cellulosic constituents, followed by nitration reaction. The effects of nitrating acid mixture type and composition, nitrating time and nitrating acid mixture to cellulose material ratio on yield and solubility of products were investigated. Results showed that alkaline resistant α -cellulose was extracted and the yield of cellulose nitrate ranged from 35.28 to 96.02%, increasing with acid mixtures HNO3 + AC2O + ACOH < HNO3 + H2SO4+ H2O < HNO3 + H3PO4 + H2O. Variation in the composition of a particular nitrating acid mixture, relative acid strength of the nitrating mixture, nitrating time and proportion of nitrating acid to cellulose material all influenced the yield and solubility of cellulose nitrate whose nitrogen contents ranged from 11.06 to 13.12%. The products were chloroform, acetone and ester soluble, hence, useful for industrial applications.